Weiterentwicklung der Forschungsdatenpraxis: Werkzeuge zur Qualitätsentwicklung für Serviceeinrichtungen in Kooperation mit Fachbereichen und Forschungsverbünden - Augsten, Marie-Theres; Bierwirth, Maik; Börner, Claudia; Dreyer, Malte; Helbig, Kerstin; Jacob, Boris; Jäckel, Denise; Kienbaum, Janna; Kuhnau, Petra; Lehmann, Anna; Paßmann, Sven; Söring, Sibylle; et al. (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2024)
After three years of project work, the DFG-funded project FDNext reflects on its results and experiences. With a focus on the further development of research data management (RDM) in daily research, the project, a cooperation of six universities in Berlin and Brandenburg, tested the specific orientation of services across institutions. Various applications focused on generic and subject-specific differentiation using different methods (train-the-trainer workshops and blended learning). Helpful tools and concepts such as a dedicated research data policy generator and a new reference model for the service management of RDM service providers were also developed. In addition, first-level legal support by RDM staff from libraries, data centers and research management was comprehensively evaluated. The project results offer valuable contributions to current RDM practices and define tasks to be addressed mutually within the community in the long-term advancement of RDM.
Keywords: Research Data Management; Disciplin-specific Research Data Management; FAIR principles